2012
DOI: 10.1016/j.devcel.2012.05.025
|View full text |Cite
|
Sign up to set email alerts
|

A Rho GTPase Signal Treadmill Backs a Contractile Array

Abstract: Contractile arrays of actin filaments (F-actin) and myosin-2 power diverse biological processes. Contractile array formation is stimulated by the Rho GTPases Rho and Cdc42; after assembly, array movement is thought to result from contraction itself. Contractile array movement and GTPase activity were analyzed during cellular wound repair, in which arrays close in association with zones of Rho and Cdc42 activity. Remarkably, contraction suppression prevents translocation of F-actin and myosin-2 without preventi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
99
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 33 publications
7
99
0
Order By: Relevance
“…2 Recent research has provided significant insights into the directional movement of vesicles, growth of cytoskeleton, and directional signaling of small GTPases. 3 An actomyosin contractile ring (controlled by concentric zones of the small GTPases Rho and Cdc42) is formed and closes to heal the cortical cytoskeleton. 3,4 The mechanisms by which vesicles move to the wound site, and how actomyosin ring contraction is initiated and controlled, are not well understood.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Recent research has provided significant insights into the directional movement of vesicles, growth of cytoskeleton, and directional signaling of small GTPases. 3 An actomyosin contractile ring (controlled by concentric zones of the small GTPases Rho and Cdc42) is formed and closes to heal the cortical cytoskeleton. 3,4 The mechanisms by which vesicles move to the wound site, and how actomyosin ring contraction is initiated and controlled, are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…3 An actomyosin contractile ring (controlled by concentric zones of the small GTPases Rho and Cdc42) is formed and closes to heal the cortical cytoskeleton. 3,4 The mechanisms by which vesicles move to the wound site, and how actomyosin ring contraction is initiated and controlled, are not well understood. Bement et al demonstrated that the centripetal signaling towards the center of the membrane breach does not depend on a myosin contraction ring.…”
Section: Introductionmentioning
confidence: 99%
“…Absence of either of these proteins prevents F-actin buildup following injury and prevents PMR, similar to the drugs that alter actin polymerization or depolymerization. 13,74 Cortical F-actin deploymerization around the injury site is followed by the recruitment of ANXA1 at the damaged PM and excision of this damaged membrane. Loss of ANXA2 and S100A11 and pharmacological inhibition of F-actin buildup prevent PMR by blocking excision of the damaged part of the PM marked by ANXA1.…”
Section: 38mentioning
confidence: 99%
“…This function of S100A11-ANXA2 complex is in agreement with work showing individual interactions of S100A11 and ANXA2 proteins with the actin cytoskeleton [46,47] . The important role of actin dynamics in this process is further supported by inhibition of PMR by drugs that block actin polymerization or depolymerization [48] . We present evidence that this is due to the role of membrane-associated cortical actin cytoskeleton in maintaining cell membrane stability [1] .…”
Section: Anxa2 and S100a11 In The Pmr Response Of Cancer Cellsmentioning
confidence: 97%